EFISIENSI ANGGARAN DALAMMANAJEMEN KEUANGAN PERGURUAN TINGGI UNTUK MENINGKATKAN KUALITAS DAN KEBERLANJUTAN INSTITUSI - Raden Minda Kusumah; Astuti Astuti (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to explore budget efficiency strategies in higher education financial management to enhance academic quality and institutional sustainability. Utilizing a descriptive analysis method with a case study approach on five higher education institutions in West Java, this research explores the implemented budget efficiency strategies and their impact on financial stability and academic quality. Data were collected through in-depth interviews with university leaders and financial managers, direct observations of budget management systems, and analysis of public documents reflecting financial transparency. The findings indicate that three universities successfully improved budget efficiency through facility optimization, performance-based workforce policies, and revenue diversification, contributing 15%–25% of their total annual budget. Meanwhile, the other two universities still face financial stability challenges due to high dependence on student tuition fees and low financial transparency, which hinder the effectiveness of budget efficiency strategies. This study concludes that universities implementing performance-based financial planning, digital financial administration, and revenue diversification tend to achieve greater financial stability. It is recommended that educational institutions establish partnerships with industries, enhance transparency in budget management, and optimize technology in financial systems. With these strategies, universities can maintain operational sustainability and improve long-term academic competitiveness.